ḤESED as Obligation: A Re-examination - Routledge, Robin (Tyndale bulletin, 1995)
While there is little dispute that ḥesed is a significant term, opinion is divided over its meaning. Glueck defines ִhesed in terms of loyalty and mutual obligation within the context of relationships, especially relationships involving a covenant. More recent studies, however, have minimised this aspect, linking ִhesed, instead, with ideas of benevolence and kindness. This article looks at the use of ִhesed in the OT in the setting of human relationships and the relationship between God and his people, and considers, too, the Hebrew terms with which ḥesed is most closely associated. It concludes in favour of the more traditional interpretation, and considers the significance of this understanding for the covenant people of God.